Diversity and distribution of euphyllidae corals in tioman island: Emphasis on the genetic variation of euphyllia cristata - Khodzori, Mohd Fikri Akmal; Saad, Shahbudin; Nordin, Noor Faizul Hadry; Salleh, Muhammad Faris; Rani, Mohd Husaini; Yusof, Muhamad Hamizan; Mohamed Noor, Normahwaty (Universiti Teknologi Malaysia, 2015)
Euphyllidae corals are among the most beautiful corals that have been exploited for the aquarium trade all over the world. In Malaysia, the information on these coral species particularly on the diversity and genetic variation is not fully documented. Realizing to this matter, the diversity and distribution of Euphylllidae corals were investigated at 13 sampling stations in Tioman Island. The diversity and distribution of Euphyllidae corals were observed and recorded using the Coral Video Transect (CVT) method. The captured images were analyzed using Coral Point Count with Excel extension (CPCe) software. The samples of Euphyllia cristata were collected at three different zones in Tioman Island (East Coast, West Coast and Isolated Island). The samples were extracted and mitochondrial Cytochrome Oxidase 1 gene primer was used to study their genetic variation. A total of six species belong to three genera of Euphyllia, Plerogyra and Physogyra were recorded. Benuang Bay (East Coast) and Bayan Bay (Isolated Island) have shown higher diversity and distribution of Euphyllidae corals among the sampling stations. The Shannon-Weinner index (H’) of Benuang Bay and Bayan Bay were 1.42 and 1.43 respectively. The West Coast zone had the lowest diversity and distribution of Euphyllidae corals due to massive coastal development and loads of human intervention. The genetic sequences from the East Coast and West Coast were closely related. The pairwise distance between these two zones is 0.003. There is a slight difference in the sequence from the Isolated Island. The pairwise distance of West Coast-Isolated and East Coast-Isolated are 0.021 and 0.025 respectively. However, it is relatively low to consider there is evolutionary divergence between the samples. Thus, no genetic variation was observed between all Euphyllia cristata taken at three different zones of Tioman Island. This study has shown that there was a highly significant difference (p<0.01) in the diversity and distribution of Euphyllidae corals with respect to sampling stations.